2004
DOI: 10.1002/mop.20015
|View full text |Cite
|
Sign up to set email alerts
|

Conception and realization of an angular optical sensor

Abstract: In this work, an angular sensor using optical fiber is achieved. The principle of attenuation of the intensity of the luminous wave in the optical fiber (curved to deduct the angle of curvature) is used. A mechanical system controlled by a PC is conceived to simulate the articulation of a human being in order to test the optical sensor on the during various angular displacements of the articulation. According to the variation of this attenuation, a measure of angle is deducted. This process may offer a useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Preliminary results revealed that such setup was feasible for a monitoring joint angular motion sensor. Two other studies showed an angle sensor whose operating principle was based on the intensity variation of the optical signal propagated through the fiber when subjected to macrobending [ 94 , 95 ]. Despite the positive results, these works had some limitations.…”
Section: Applicationsmentioning
confidence: 99%
“…Preliminary results revealed that such setup was feasible for a monitoring joint angular motion sensor. Two other studies showed an angle sensor whose operating principle was based on the intensity variation of the optical signal propagated through the fiber when subjected to macrobending [ 94 , 95 ]. Despite the positive results, these works had some limitations.…”
Section: Applicationsmentioning
confidence: 99%
“…In reality, in comparison with these electrical counterparts, fiber-optic sensors are increasingly used for human joint monitoring, because of the advantages of small size, light weight, flexibility, versatility and immunity to external electromagnetic interference [14]. Moreover, compared with the fabricated electrical fibers in reference [13], optical fibers can be more easily achieved by a controllable machining process.…”
Section: Introductionmentioning
confidence: 99%
“…However, these conventional POF sensors usually demonstrate low bending sensitivity, especially at lower bending deformation, regardless of the fluctuations in detected power. According to previously published work [14], these external power disturbances related to intensity-based sensors can be compensated for, nonetheless, by various intensity referencing schemes. In order to enhance the sensitivity of a bent POF sensor, a simple side-polishing method is generally adapted, because the mechanical resistance of the fiber allows an easy removal of a portion of the jacket, cladding and core [23].…”
Section: Introductionmentioning
confidence: 99%
“…Optical fibers are wrapped around the body, and light loss occurs due to a change in the curvature radius of the optical fiber when the joint angle increases. The change in the joint angle can be indirectly measured by the loss of light intensity [24][25]. This type of sensor has a small measurement range and is difficult to adapt to large joint motion [25].…”
Section: Introductionmentioning
confidence: 99%